SUBTLE AND BLATANT PREJUDICE SCALES: ONE OR TWO DIMENSIONS? - Javaloy, Federico; Cornejo, José Manuel (Anales de Psicología / Annals of Psychology, 2006)
This paper examines whether the blatant and subtle prejudice scales of Pettigrew and Meertens (1995) are truly independent. We consider the correlation, factor structure and predictive capacity of the type of prejudice that these scales identify. In this study, subjects were administered the questionnaire and then placed in an experimental courtroom simulation, in which they act as members of the jury. The simulation stage, which represented the main innovation of the study, provided additional information on the validity of the typology. The data obtained showed a high correlation between the two scales and a factor structure that also calls into question the idea that the blatant and subtle prejudice scales are two independent dimensions. On the other hand, the typology presents a certain predictive value. All this suggests that the two scales reflect different levels of intensity of the same construct.